Ultrastructural description of rabies virus infection in cultured sensory neurons (2007)
Primary cultures were made from adult mouse spinal ganglia for depicting an ultrastructural description of rabies virus (RABV) infection in adult mouse sensory neuron cultures; they were infected with rabies virus for 24, 36, and 48 h. The monolayers were processed for transmission electron microscopy and immunochemistry studies at the end of each period. As previously reported, sensory neurons showed great susceptibility to infection by RABV; however, in none of the periods evaluated were assembled virions observed in the cytoplasm or seen to be associated with the cytoplasmic membrane. Instead, fibril matrices of aggregated ribonucleoprotein were detected in the cytoplasm. When infected culture lysate were inoculated into normal animals via intra-cerebral route it was observed that these animals developed clinical symptoms characteristic of infection and transmission electron microscopy revealed assembled virions in the cerebral cortex and other areas of the brain. Sensory neurons infected in vitro by RABV produced a large amount of unassembled viral ribonucleoprotein. However, this intracellular material was able to produce infection and virions on being intra-cerebrally inoculated. It can thus be suggested that the lack of intracellular assembly in sensory neurons forms part of an efficient dissemination strategy.